Is there an increased complications rate in after-hours colorectal surgery? - Bogdan Socea; Oana Halau; Ovidiu Gabriel Bratu; Alexandru Constantin Carap; Tiberiu Paul Neagu; Dumitru Cristinel Badiu; Vlad Denis Constantin (Modern Medicine)
When a surgical team is dealing with an after-hours colorectal surgery, they are actually confronting with a chain of elements and events, some linked to the patient and severity of the surgical case, others related to the medical team ability to cooperate, from nurses to surgeon and anesthetist. There is a series of differences between elective and emergency performed surgeries, two of them and most important elements are the patient (disease type, age, preoperative condition) and the operating team (experience, technical performance after-hours, especially at night).